THE SELECTION IMPROVEMENT IN THE THIRD JUNIORS HANDBALL TEAM - Dugan Iulian (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
From 10-14 years to the child through one of the most important stage of ontogenesis. Childhood ends and begins transformation of nature: somatic-functional-mental-driving. This processor is called puberty.